Classification system of seizures and epilepsy - Sirven, Joseph (Henry Stewart Talks, 2011)
Classification of Seizures and Epilepsy, How are seizures and Epilepsy Classified?, Proposed Changes to the Classification system, What does the future hold for Classification?
Updated at 2020/06/30